Parotitis lithiasis in children rare cause of recurrent parotid swelling in children - BELHAJ, NAJOUA; I.BOUMENDIL; H.RAHIM; I.ALLOUCH; R.BENCHEIKH; M.A.BENBOUZID; L.ESSAKALLI (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
in pediatrics, the parotid lodge is known for its infectious pathology dominated by mumps parotitis and recurrent microbial parotitis. Conversely, tumor pathology plays a more modest role, but lithiasic origin not to be eliminated .We report in this work he observation of a child who presented episodes of recurrent parotid swellings whose etiological balance returned in favor of the lithiasic origin